Digital trade and global environmental quality: The moderating role of energy justice - Muhammad Tariq Majeed; Maryum Bashir; Samina Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2026)
The potential of digital trade (DTE) and energy justice (EJ) to support environmental quality requires in-depth exploration because the environmental gains of DTE can be compromised in economies where EJ is not ensured. This study explores the environmental effects of DTE and EJ on ecological footprint (EF) utilizing panel data from 147 economies from 2005 to 2023. The empirical results are estimated using panel data estimators namely fixed effects, random effects, the system generalized method of moments (GMM) and the method of moments quantile regression (MMQR). The GMM estimates suggest that DTE exerts a positive and significant influence on the environment. However, the MMQR results demonstrate that the effect of DTE on EF varies in sign and magnitude across quantiles. The positive effect is observed in median and higher quantiles while the negative effect is noted in lower quantiles. Finally, the results suggest a moderating role of EJ in the environmental effect of DTE. That is, the interactive effect of DT with EJ exerts a significantly positive effect on environmental quality. This finding suggests that ensuring EJ in home economies strengthens the environmental benefits of digital trade integration. These findings offer important policy implications for advancing digitalization strategies along with ensuring EJ to promote global environmental sustainability.
Keywords: 330; Digital trade; ecological footprint; energy justice; environmental quality; resource endowment